A tipi yatırım fonlarında etkin bir nakit yönetim stratejisi oluşturmada analitik hiyerarşi yaklaşımı - Yolal, Feral (Fen Bilimleri Enstitüsü, 1998)
Para ve sermaye piyasaları fonların finansal araçlar aracılığı ile tasarruf fazlası olan kesimden, daha fazla fona ihtiyaç duyan yatırımcı kesimlere en az maliyetle aktarılmaya çalışıldığı yerlerdir. Sermaye piyasası araçlarından biri olan yatırım fonları ülkemizde yeni yeni tanınmakta ve gelişmekte olmaları sebebi ile de öncelikle derinlemesine incelenmeye ihtiyaç duyulmaktadırlar. Çalışmanın birinci bölümünde, Analitik Hiyerarşi Prosesi ile ilgili olarak yapılmış literatür çalışmasına yer verilmiştir. Yöntemin ana hatları ile incelendiği bu bölümde Analitik Hiyerarşi Prosesi'nin matematiksel temeli de kısaca irdelenmiştir. İkinci bölümde, kısaca yüzeysel bir bilgi edinilmesi amacına yönelik olarak grup karar verme tekniklerinden bahsedilmiştir. Üçüncü ve dördüncü bölümlerde ise yatırım fonları hakkında genel bilgilerin verilmesinin ardından çalışmanın temelini oluşturan A Tipi Hisse Senedi Fonları'nın kuruluş aşaması, içtüzükleri, diğer tip fonlardan farkları ve fonun işleyişi gibi detaylar tümü ile açıklanmıştır. Beşinci bölümde de Analitik Hiyerarşi Prosesi'nden yararlanılarak A Tipi yatırım fonlarındaki yüksek miktarda giriş-çıkışların getiride meydana getirdiği düzensizlikleri çözmeye yönelik bir uygulamaya yer verilmiştir. Sonuçlar ve öneriler kısmında da çalışmadan elde edilen sonuçlar derlenmiş ve bazı öneriler üzerinde durulmuştur.

Sigmund Freud was once asked by an interviewer how he made decisions. He responded by taking a coin out of his pocket and saying that he flipped it. The interviewer was agitated and said, "What! You, the great psychologist, toss a coin to make a decision?" Freud replied, "Yes, I toss the coin and see if I like the way it turns up." The first chapter of this master thesis is dedicated to a basic literature survey about Analytic Hierarchy Process. The Future Depends on the Quality of the Decisions Assigning priorities, evaluating variables, making and justifying tough trade-offs, integrating multiple points of view are all part of the daily decisions. The quality of these decisions is critical to our success and to the success of those who depend on us. Unfortunately as decisions become more complex -with more alternatives, more criteria and more variables- the ability to mentally manage, relate and evaluate all the elements deteriorates. As a result, it is preferable to focus the attention on just a few factors to prevent to weaken the ability to reach the best overall conclusion. The Logical Choice for Better Decision Making Thomas L. Saaty, creator of the Analytic Hierarchy Process (AHP), the most comprehensive and widely used decision support system in the world, said that "Our present complex environment calls for a new logic -a new way to cope with the myriad factors that affect the judgments we make and the conclusions we draw. This approach should be justifiable, easy to apply and appeal to our good sense. " XI AHP is used worldwide in dozen of corporations and agencies, including the U.S. State Department, U.S. Department of Defense, U.S. Air Force, Xerox, Boeing, Merck, General Electric, Conoco Oil, Rockwell International, The World Bank, Citibank and the governments of the United States, Canada, South Africa, Singapore, Indonesia, China and Kuwait. Improve the Decision Making with the Structured Approach The Analytic Hierarchy Process enhances decision making by providing a logical, easy-to-use framework in which all the elements of a decision can be defined, organized and carefully evaluated. Designed to reflect the way people actually think, the AHP was developed more than 20 years ago by Thomas L. Saaty and continues to be the most highly regarded and widely used decision-making theory in use. With the AHP, the objectives, alternatives and criteria are arranged in a hierarchical structure similar to a family tree. The process of building this structure not only helps to identify all the elements of the decision more accurately, but also to recognize the interrelationships between them. Accommodates both Hard Data and Intuition Among the factors that make the AHP the world's most popular decision support theory, is that it accommodates hard data -such as costs, interest rates and dimensions- as well as personal judgment and intuition. It also permits to derive relative, mathematically-based weights for the criteria, instead of having to guess or randomly assign weights to variables, as other decision analysis techniques do. By reducing complex decisions to a series of simple comparisons and rankings, then synthesizing the results, the AHP not only helps to arrive at the best decision, but also provides a clear rationale for the choice made. Analytic Hierarchy Process has proven successful in improving decision making in a broad range of areas, including: Benefit/Cost Analysis, Resource Allocation, Risk Analysis, Strategic Planning, Performance Evaluations, Environmental Decision Making, TQM/Business Process Re-engineering, Negotiation and Conflict Resolution, Project Management, Marketing Decisions, Acquisition/Merger Evaluation, Product Research and Development, Customer Satisfaction, Site Selection or Relocation, Predicting Outcomes of Recommended Policies, What-if Forecasting... The entire AHP process involves defining the pros and cons of various alternatives, organizing the objectives and goals, developing the decision hierarchy, synthesizing the results, examining how modifying the variables affects the results. XII After identifying the objectives, the alternatives and the criteria on which the alternatives will be judged, the relative importance of each criterion and alternative could be weighted by using the judgments made by specialists. In the real world of decision making, intangible factors -such as the financial risk involved in an acquisition or the impact of a change in the political climate- are often more important than factors that can be measured. So Analytic Hierarchy Process enables people to effectively combine both measurable and subjective factors in the decision process. Decision Simplified to One-on-one Comparisons Once the model is complete, AHP poses a series of simple comparisons of the alternatives in relation to the criteria and objectives depending on the person own preferred way of working. The judgments may be in numerical or verbal mode because verbal judgments could be easily transformed in numerical data using a special scale. AHP Synthesizes the Knowledge and Judgments to Find the Best Decision Once all the comparisons have been made, it 's time to process the data, to synthesize the judgments, and to calculate the priorities that shows how the alternatives are ranked. A consistency check to identify any inconsistencies in the judgments -such as A is better than B, and B is better than C, but C is better than A- then reconsidering the judgments, revising them and seeing how this affects the decision become a necessity. Investigate "What-if" Scenarios If the relative weights of the criteria -or, as with most complex decisions, they may be subject to change-, sensitivity analysis charts must be prepared to let to see quickly and graphically how altering the weights of the criteria changes the results of the decision-making process. Bring Together Knowledge and Experience From Multiple Source Within today's organizations, decisions are increasingly being made by groups rather than individuals, and AHP is especially effective at coordinating complex decision-making input from multiple group members. Members don't have to agree on the relative importance of the criteria or the rankings of the alternatives. Each member can make his or her judgments, and makes a distinct, identifiable contribution to a jointly-reached conclusion. XIII The second chapter of this study is about group decision making. Group Decision Making It has been proven by research that individuals, when working within a group, are better at idea generation when they can generate ideas anonymously and in silence, than when they have to "go public" with their ideas during the generation phase. Most Brainstorming/Brainwriting techniques rely on the rules developed by Alex Osborne during his research into Brainstorming. These rules are: 1. Defer Judgment Do not criticise or praise ideas as they are presented, there is a time and place for a critical review of ideas generated, but the idea generation phase is not it. More ideas are generated when criticism is deferred. 2. Quantity Breeds Quality The more ideas that are generated, the more the chance there is that the best ideas will be chosen. 3. The wilder the Idea the Better Breakthrough ideas are needed to produce new insights. Although it might not be possible to implement the wild idea, it might be possible to implement a modification to the idea. A cautious conservative approach is not likely to produce breakthrough ideas. 4. Combine and Improve Ideas The principle of "piggybacking" or using a combination of ideas to generate new ideas is a sound one. 5. Take a Break from the Problem Sometimes it is possible to get so involved in idea generation that minds tire and thinking is inhibited. It is best to take breaks after 20 to 30 minutes when generating ideas. Brainwriting is a highly effective group method of gaining understanding into complex situation, it is also very good for producing Group Learning and helping the Team Building process. It is important that the rules for the entire process are explained to the group before the session starts. Mutual Funds, the subject of the third and fourth chapter, have in recent years, become among the most talked about and written about investments available to the general public. What's a Mutual Fund? A mutual fund is a pool of money belonging to a number of investors that is managed on their behalf by professional money managers. Every mutual fund is divided up into equal sized units, much like the ownership of a XIV company is divided up into equal sized shares. This allows individual investors to own a relatively small share of a larger pool of diversified assets at a relatively low cost. Every mutual fund has a stated investment objective that guides the portfolio manager in determining the best assets to hold in a particular fund. Depending on their investment objectives, mutual funds can invest in many different financial instruments, including domestic and foreign stocks, bonds, treasury-bills, or a mix of many of these different assets and also they have different names depending on these financial instruments. Professional Management One of the most important features of a mutual fund is its professional management. A full-time professional manager or management team is using their expertise day in and day out to maximize the returns and minimize the risks of the investment category selected. These individuals have a considerable amount of experience at managing large portfolios of securities within the investment objectives of the fund. Diversification With mutual funds, the investor's money is "pooled" with potentially thousands of others and the investor owns a pro-rated share of the pool. This pool is then invested in stocks and/or bonds of which allow the fund manager to meet the fund's objectives. The investor's investment, as a part of the mutual fund pool, is spread out over dozens or even hundreds of individual investments. As a result, the investor achieve a level of diversification that most ordinary investors cannot achieve on their own. Beyond the diversification feature of each individual fund, the investor can also use mutual funds to diversify his or her portfolio as a whole. Redeeming Mutual Funds If an investor should decide to sell all or portion of the mutual funds that he or she owns, he or she can sell it on any business day. In some mutual funds the investors should place an order to sell frequently valid after two weekdays. There is no other condition in redeeming mutual funds. Making Money with Mutual Funds Mutual Funds can make money for their investors in a couple of different ways. A mutual fund is nothing than a large pool of investments in various financial instruments such as stocks or bonds. Those underlying investments can generate interest or dividends that get paid to the fund. This income, if there is any, is distributed to the investors in the mutual fund on a fairly regular basis. The other way that mutual funds make money is capital appreciation. Every day, each of the underlying assets are valued, and when added together, give a Total Asset Value for the fund. When the XV Total Asset Value of the fund is divided by the number of units outstanding, the Net Asset Value Per Share which also acts as the Unit Price is obtained. As the value of the underlying assets increases, so too does the unit price of the fund. This capital appreciation remains unrealized until the mutual fund investor sells his or her units in the fund. Types of Mutual Funds A distinctive classification is basically used for the mutual funds: Type A and Type B. The difference between these two types is that Type A mutual funds must invest at least 25% of their Total Asset Value in stocks to obtain a tax shelter. There are also many different types of mutual funds to choose from. Besides being Type A or B, mutual funds are generally distinguished by the type of assets they hold, as determined by their investment objectives. Here are some general categories we can use to classify virtually all mutual funds in Turkey. Notes'n Bonds Funds, Equity Funds, Sector Rotation Funds, Golden and Precious Metals Funds, Affilliate Companies Funds, Group Funds, Foreign Securities Mutual Funds, Liquid Funds, Variable Funds, Balanced Funds, Index Funds, Private Funds Risk and Reward The value and returns of mutual funds over time are not fixed. They can and almost always do fluctuate over time. The majority of people invested in mutual funds for the long term are rewarded with good returns. It is possible, depending on when you buy and when you sell, that the returns on a mutual fund can be negative. The Costs Associated with Mutual Funds There are one potential and important cost associated with mutual funds: The ongoing management and administrative expenses charged to the funds. Mutual funds are operated by professional investment managers whose services are paid for directly by the fund. These "management fees", as they are termed, will vary typically between 0.008% and 0.015% of Total Net Asset Value. The other expenses of operating a mutual fund, such as legal, audit and administrative fees are also usually paid for by the fund. Together with the management fees, there are some other expenses, including brokerage commissions, interest charges and taxes, if any. The fifth chapter demonstrates how the use of the Analytic Hierarchy Process (AHP) can be useful in finding a way to solve the yield and liquidity XVI problem of the type A mutual funds. The factors which affect this problem are analysed in a hierarchy having 5 levels. The hierarchy is constructed by the decision group chosen between the staff of Tekstil Menkul Değerler AŞ., with an external perspective about the problem. Brainwriting session which allows the group to focus on the task of generating pairwise comparison matrices for the criteria and alternatives, was preferred by the decision group because the method eliminates the dominance by strong personalities and the influence of opinion-leaders. The elements in a level are compared against all others in the same level with respect to the elements on the preceding level. These comparisons are then arranged as reciprocal matrices. The main diagonal of these matrices is always equal to unity. Once the matrices in each level are completed, the relative importance of the elements in that level is given by the principal right eigenvector of the matrix of judgments. The components of each eigenvector sum to unity. Thus a percentage of priority to each factor at each level can be effectively attributed. At the end, the composite priority of the alternatives at the fifth level with respect to all the criteria at the fourth level is obtained by multiplying the priorities of the alternatives under each criterion by the priority of the criterion and adding across criteria. In order to control the result of the method, the consistency ratio for each of the matrices and the overall inconsistency for the hierarchy are calculated. These numbers are less than 0.10, in other words, they are within the acceptable range of consistency. In order to have an idea of the stability of the rankings to the changes that can be contemplated in the weight of the criteria, a sensitivity analysis was also conducted. At the end, it is concluded that "a new and efficient mutual fund management team" alternative is the solution of the problem. But it is a not the only dominant alternative. The "order to sell" alternative despite the fact that it is not economical for the investors, has also obtained a remarkable success because of its controlling of the liquidity of the fund. The objective of this master thesis named "Developing an Efficient Type A Mutual Fund Cash Management Strategy's through Analytic Hierarchy Process (AHP) Method" is to be a guide for the future new and detailed studies made about type A mutual fund's yield problem. It may also have a role of pre-research for the people interested in that subject.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Keywords: Analitik hiyerarşi süreci; Nakit yönetimi; Yatırım fonları; Analytical hierarchy process; Cash management; Mutual funds